2019
DOI: 10.1016/j.ajic.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the successful implementation of disinfecting port protectors to reduce CLABSI in a large tertiary care teaching hospital

Abstract: HIGHLIGHTS • Disinfecting port protectors can be used to reduce CLABSI. • Implementation of port protectors into nursing culture can be challenging. • Evidence-based strategies for implementation can be utilized to sustain their use. Disinfecting port protectors are a supplement to the central line-associated bloodstream infection prevention bundle as an optional recommendation from the Centers for Disease Control and Prevention. Despite evidence of effectiveness, few centers have successfully reported systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This reduction resulted in a total cost savings of $1,636,792 due to 27 fewer CLABSIs, after considering the added cost of the port protectors. 10 Furthermore, meta-analyses have consistently shown that disinfecting caps can reduce CLABSI rates by 41-57% compared to scrubbing the hub and generate median cost savings of $21,890 per CLABSI. [11][12][13][14] Additionally, studies have indicated that disinfecting caps can enhance the effectiveness of CLABSI prevention bundles.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction resulted in a total cost savings of $1,636,792 due to 27 fewer CLABSIs, after considering the added cost of the port protectors. 10 Furthermore, meta-analyses have consistently shown that disinfecting caps can reduce CLABSI rates by 41-57% compared to scrubbing the hub and generate median cost savings of $21,890 per CLABSI. [11][12][13][14] Additionally, studies have indicated that disinfecting caps can enhance the effectiveness of CLABSI prevention bundles.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 7 years, the guide has been requested from our organization’s website over 5000 times from 51 countries and all US states, cited over 100 times, and translated into several languages. The framework has been cited as supporting EBP change and organizational EBP programming, and as supporting the need for research or affirming the phased, yet iterative nature of implementation and the need to address organizational support [ 41 47 ]. Strategies have been operationalized with definitions, actionable procedures, and examples, to promote effective use and improve implementation outcomes in a monograph entitled Evidence-Based Practice in Action [ 33 ].…”
Section: Introductionmentioning
confidence: 99%